Discourse on Women's Leadership in the Qur’an from the Perspective of KH. Ahmad Bahauddin Nursalim on Youtube Channel - Moh Alfin Rosyidi; Khobirul Amru; Wildah Nurul Islami (Bulletin of Indonesian Islamic Studies, 2025)
Leadership remains a debated topic within Islamic discourse, particularly concerning the role of women. This discussion is significantly shaped by traditional interpretations of the Qur'an, which often place women in subordinate positions. This article aims to examine how KH. Ahmad Bahauddin Nursalim offers an inclusive interpretation of women's leadership based on Surah al-Naml, verses 41–44. The study employs a qualitative method alongside a descriptive-analytical approach, with data collected through observation and note-taking from five videos across four accounts featuring presentations by KH. Ahmad Bahauddin Nursalim. The analysis uses Teun A. Van Dijk's discourse analysis theory, which focuses on three key aspects: text, social cognition, and social context. The findings indicate that traditional leadership roles are largely portrayed as favoring men, who are anticipated to be responsible and just, as revealed through textual analysis. The social cognition analysis investigates how KH. Ahmad Bahauddin Nursalim’s interpretation responds to the rising visibility of women in leadership, shedding light on Sharia-based legal perspectives regarding female leadership. Furthermore, in the social context dimension, he contends that women can assume leadership roles as long as they uphold moral boundaries and act justly. The study also highlights the crucial role of social media in disseminating contemporary religious discourse and shaping public reactions to Qur'anic reinterpretations in the digital age.